2012
DOI: 10.6026/97320630008834
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and virtual screening for novel protein tyrosine phosphatase 1B (PTP1B) inhibitors

Abstract: Protein tyrosine phosphatase 1B (PTP1B) functions as major negative regulator of insulin and leptin signaling pathways. In view of this, PTP1B is an significant target for drug development against cancer, diabetes and obesity. The aim of the current study is to identify PTP1B inhibitors by means of virtual screening with docking. 523,366 molecules from ZINC database have been screened and based on DOCK grid scores and hydrogen bonding interactions five new potential inhibitors were identified. ZINC12502589, ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…To date, some bioinformatics results focusing on the reversal of leptin resistance have been carried out. For example some papers have reported molecules with the ability to inhibit PTP1B , whereas no results against SOCS3 and SH2B1 have been found. Following this virtual screening, the selected set of molecules that fulfil the prerequisites should be used in an in vitro assay to confirm the theoretical activity described.…”
Section: Methods For the Identification Of New Natural Compounds Withmentioning
confidence: 99%
“…To date, some bioinformatics results focusing on the reversal of leptin resistance have been carried out. For example some papers have reported molecules with the ability to inhibit PTP1B , whereas no results against SOCS3 and SH2B1 have been found. Following this virtual screening, the selected set of molecules that fulfil the prerequisites should be used in an in vitro assay to confirm the theoretical activity described.…”
Section: Methods For the Identification Of New Natural Compounds Withmentioning
confidence: 99%
“…Recent advances in modern molecular biological tools like DNA sequencing, genetic engineering, gene targeting and transgenic methodologies have showed a new path to better understand and analyze the infections, diseases and disorders, which provides novel options for developing new age therapeutics [15][16][17][18]. Presently, to fight with diseases like cancer [15][16][17][18][19] and disorders like diabetes [20], numerous efficient drug development technologies have been established through programs like in silico drug designing as well as synthesis of various novel molecules [5,[21][22][23][24], however the problems continue the same. Therefore alternatives are required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Zn signaling regulates kinase and phosphatase function (39,40). Protein tyrosine phosphatase 1B (PTP1B) is a major negative regulator of the insulin and leptin signaling pathways and is an important therapeutic target for diabetes and obesity, and Zn ions inhibit its activity (102). Therefore, MTs were assumed to attenuate the inhibitory effects of Zn ions on PTP1B activity by sequestrating Zn, followed by dephosphorylation of STAT1 and STAT3 by PTP1B to inhibit IL-27-induced Tr1-cell differentiation (123).…”
Section: Different Effects Of Intracellular and Extracellular Mts On mentioning
confidence: 99%